Physiological and proteomic insights into melatonin-mediated delay in postharvest quality deterioration of blue honeysuckle fruit - Ruiling Liu; Lun Tao; Xiangjun Fang; Chaoyi Shen; Junwei Huo; Maratab Ali; Huizhi Chen; Hailong Yang; Haiyan Gao (Postharvest Biology and Technology, 2026)

Mitochondrial dysfunction in hypertension: mechanistic pathways and therapeutic implications - Jiao Tian; Lin Yi; Yuyuan Lu; Yushun Kou; Lingna Zhang; Penghui Jin; Xiaoke Wang; Tao Wu; Xin Yang; Yiyuan Wang; Ruiling Ma (Functional & Integrative Genomics, 2026)

Agricultural greenhouse gas emissions in the Yangtze River Economic Belt of China - Guichi Zhang; Lei Tang; Xiaoqi Zheng; Feng Yang; Ruiling Sun (Applied Soil Ecology, 2026)

Selective iron removal from Fe-PGMs alloys for platinum group metals concentration: Dissolution behavior of PGMs and ultrasound-assisted leaching - Han Yang; Yong Li; Xilong Wu; Ruiling Yuan; Chao Wang; Shengnan Lin; Jibiao Han; Kuo Liu (Journal of Environmental Chemical Engineering, 2026)

Modulation of hyporheic exchange and solute transport by plant cluster configurations - Siyi Zhang; Yihang Yang; Yuhang Tian; Ruiling Long; Kaiwen Zhang; Guangqiu Jin; Xinyi Luo; Guiqiao Wang (Advances in Water Resources, 2026)

Effects and mechanisms of different metastable systems on the interfacial stability and physicochemical properties of ovalbumin emulsion gels - Zongqi Yang; Lili Shi; Ruiling Li; Yi Song (Food Chemistry, 2026)

Effect of liquid-medium properties on ultrasound inactivation efficiency and mechanism against Escherichia coli and Listeria monocytogenes - Bin Yang; Tingting Chen; Ruyu Zhang; Haiqi Chen; Wenjun Wang; Ruiling Lv; Donghong Liu (Food Bioscience, 2026)

Separation and enrichment of platinum from spent petroleum reforming catalysts via carrier-directed dissolution under alkaline conditions - Qingfeng Xiong; Han Yang; Lang Liu; Jibiao Han; Yu Shen; Wenhui Ma; Yakun Zhang; Ruiling Yuan; Chao Wang (Journal of Environmental Chemical Engineering, 2026)

Performance evaluation of sulfur autotrophic denitrification technology, AO process and anaerobic MBR for treating real mineral processing wastewater - Yilin Shang; Ruiling Luo; Yue Yang; Jiansheng Li (Journal of Environmental Chemical Engineering, 2026)

State-of-the-art insights into hydrogel innovations from structural engineering to smart preservation: Research trends and future directions - Yan Xu; Yiyi Cheng; Tao Yang; Huizhi Chen; Ben Niu; Xiangjun Fang; Weijie Wu; Chaoyi Shen; Guannan Wang; Bangdi Liu; Ruiling Liu; Haiyan Gao (Trends in Food Science & Technology, 2026)

Exploring the potential of ultrasound to improve the physicochemical properties of protein-based emulsion gels: by ultrasonically treating emulsion (pre-emulsification, post-emulsification) and substrate solution respectively - Ruiling Li; Chao Ma; Ningzhe Wang; Jing Wang; Xin Yang (Food Hydrocolloids, 2025)

Effect and mechanism of ultrasound time and storage time on physicochemical properties, 3D printing accuracy, and microstructure of ovalbumin–gellan gum emulsion gels - Ruiling Li; Ningzhe Wang; Chao Ma; Jiacheng Wang; Jing Wang; Xin Yang (Food Chemistry, 2025)

The anti-Alzheimer's disease effects of ganoderic acid A by inhibiting ferroptosis-lipid peroxidation via activation of the NRF2/SLC7A11/GPX4 signaling pathway - Qingyang Lu; Nan Shao; Ziyi Fang; Zhaorong Ouyang; Yiran Shen; Ruiling Yang; Houli Liu; Biao Cai; Tao Wei (Chemico-Biological Interactions, 2025)

Fe-loaded hollow fiber carbon microfiltration membrane and its BPA removal performance based on electro-Fenton - Ruiling Luo; Zhongcheng Yang; Yucheng Wang; Yue Yang; Lanyue Qi; Junwen Qi; Zhigao Zhu; Yujun Zhou; Jiansheng Li (Journal of Environmental Chemical Engineering, 2025)

Characterization of a betaendornavirus isolated from the edible fungus Morchella sextelata - Ruiling Lyu; Junlin Chen; Qing Tang; Du Hai; Tun Wu; Huagang Xiao; Jiatao Xie; Yang Xiao (Archives of Virology, 2025)

Construction and formation mechanism of phase-change polysaccharide–protein composite emulsion gels: For simultaneous printing of food products with complex structures and fine patterns - Ruiling Li; Ningzhe Wang; Chao Ma; Jiacheng Wang; Jing Wang; Xin Yang (Food Hydrocolloids, 2025)

Shiitake mushroom-derived extracellular nanovesicles: Preparation, characterization, and inhibition of Caco-2 cells - Xueli Yang; Zihao Zong; Ben Niu; Hangjun Chen; Weijie Wu; Xiangjun Fang; Ruiling Liu; Haiyan Gao; Honglei Mu (Food Chemistry, 2025)

Silk protein: A novel antifungal and edible coating for strawberry preservation - Yan Wang; Weijie Wu; Ruiling Liu; Ben Niu; Xiangjun Fang; Hangjun Chen; Mohamed A. Farag; Li-Shu Wang; Guannan Wang; Hailong Yang; Huizhi Chen; Haiyan Gao (Food Chemistry, 2025)

The physicochemical properties of oat starch-fatty acid complexes and application in Lactiplantibacillus plantarum microencapsulation - Jiaqi Wu; Yi Yang; Lianger Dong; Ruiling Shen (Food Bioscience, 2025)

Mechanical behavior and compositional variation of weathered granite soil with different degrees of weathering - Yi Shan; Kezheng Yang; Ruiling Jia; Yadong Li; Yizhao Wang; Jie Cui (Bulletin of Engineering Geology and the Environment, 2025)

Recent advances in Zizania latifolia : A comprehensive review on phytochemical, health benefits and applications that maximize its value - Weijie Wu; Yanchao Han; Ben Niu; Baiqi Yang; Ruiling Liu; Xiangjun Fang; Huizhi Chen; Shangyue Xiao; Mohamed A. Farag; Shiqi Zheng; Jianbo Xiao; Hangjun Chen; et al. (Critical Reviews in Food Science and Nutrition, 2024)

A novel function of benzoic acid to enhance intestinal barrier defense against PEDV infection in Piglets - Ruiling Liu; Rongfeng Tang; Yuchen Li; Qiu Zhong; Yunlei Cao; Qian Yang (Veterinary Microbiology, 2024)

Simulated gastrointestinal digestion of walnut protein yields anti-inflammatory peptides - Wei Xia; Yuan Gao; Xiangjun Fang; Long Jin; Ruiling Liu; Li-Shu Wang; Yangyong Deng; Junlong Gao; Hailong Yang; Weijie Wu; Haiyan Gao (Food Chemistry, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Failure probability estimation of natural gas pipelines due to hydrogen embrittlement using an improved fuzzy fault tree approach - Guojin Qin; Ruiling Li; Ming Yang; Bohong Wang; Pingan Ni; Yihuan Wang (Journal of Cleaner Production, 2024)

4D food printing: Key factors and optimization strategies - Ningzhe Wang; Ruiling Li; Xibo Wang; Xin Yang (Trends in Food Science & Technology, 2024)

Nanoparticle encapsulation using self-assembly abietic acid to improve oral bioavailability of curcumin - Ying Han; Hua Zhang; Haitian Zhao; Shiyao Fu; Ruiling Li; Zhili Wang; Yangxin Wang; Weihong Lu; Xin Yang (Food Chemistry, 2024)

The association between neuropsychiatric effects of substance use and occurrence of endoplasmic reticulum and unfolded protein response: A systematic review - Bin Yang; Ruiling Zhang; Mohammad Farris Iman Leong Bin Abdullah (Toxicology Letters, 2024)

Critical taste substances and regulatory pathways of fresh lotus seed pulps at different ripeness stages - Yinai Yang; Ruiling Liu; Yanchao Han; Weijie Wu; Xiangjun Fang; Honglei Mu; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2023)

Enhanced viability of probiotics in composite hydrogel beads - Fan Zhang; Ruiling Wang; Lichen Zhang; Lei Yan; Yuze Jia; Jie Yang; Xin Wang; Xin Lü (Journal of Food Engineering, 2023)

Protein-based emulsion gels as materials for delivery of bioactive substances: Formation, structures, applications and challenges - Ruiling Li; Yong Guo; Aijun Dong; Xin Yang (Food Hydrocolloids, 2023)

Effect of influent ammonia nitrogen concentration on the phosphorus removal process in the aerobic granular sludge reactor - Wei Cheng; Cong Ma; Ruiling Bao; Xiaoli Yang; Xuankai Zhou; Yan Liu; Qing Liu; Aidong Ruan; Xiang Li (Journal of Environmental Chemical Engineering, 2023)

Advances of stable isotope technology in food safety analysis and nutrient metabolism research - Wei Xia; Xiangjun Fang; Yuan Gao; Weijie Wu; Yanchao Han; Ruiling Liu; Hailong Yang; Hangjun Chen; Haiyan Gao (Food Chemistry, 2023)

Regulating cobalt chemical state by CeO2 facets preferred exposure for improved ethanol steam reforming - Ruiling Li; Chengyuan Liu; Li Li; Junjie Xu; Jinjin Ma; Jiaqi Ni; Jing Yan; Jun Han; Yang Pan; Yi Liu; Lilin Lu (Fuel, 2023)

Application of melatonin delays lignification in postharvest water bamboo shoots in association with energy metabolism - Baiqi Yang; Yanchao Han; Haiyan Gao; Ruiling Liu; Feng Xu; Ruihai Liu; Shangyue Xiao; Bin Li; Hangjun Chen (Postharvest Biology and Technology, 2023)

Complete genome sequence of Edgeworthia chrysantha mosaic-associated virus, a tentative new member of the genus Coguvirus (family Phenuiviridae) - Xiaoru Wang; Ruiling Liao; Xinying Yang; Qiyan Liu; Song Zhang; Mengji Cao (Archives of Virology, 2022)

Treatment of Wastewater-CPL by Biochar-Based Fenton-Like Catalyst in the Presence of Micro-nano Bubbles - Ruiling Zhang; Jiajun Wang; Jianyu Yang; Songyan Qin; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2022)

Soil phosphorus drives plant trait variations in a mature subtropical forest - Erqian Cui; Ruiling Lu; Xiaoni Xu; Huanfa Sun; Yang Qiao; Jiaye Ping; Shuying Qiu; Yihua Lin; Jiehuan Bao; Yutong Yong; Zemei Zheng; Enrong Yan; et al. (Global Change Biology, 2022)
Earth system models are implementing soil phosphorus dynamic and plant functional traits to predict functional changes in global forests. However, the linkage between soil phosphorus and plant traits lacks empirical evidence, especially in mature forests. Here, we examined the soil phosphorus constraint on plant functional traits in a mature subtropical forest based on observations of 9943 individuals from 90 species in a 5‐ha forest dynamic plot and 405 individuals from 15 species in an adjacent 10‐year nutrient‐addition experiment. We first confirmed a pervasive phosphorus limitation on subtropical tree growth based on leaf N:P ratios. Then, we found that soil phosphorus dominated multidimensional trait variations in the 5‐ha forest dynamic plot. Soil phosphorus content explained 44% and 53% of the variance in the traits defining the main functional space across species and communities, respectively. Lastly, we found much stronger phosphorus effects on most plant functional traits than nitrogen at both species and community levels in the 10‐year nutrient‐addition experiment. This study provides evidence for the consistent pattern of soil phosphorus constraint on plant trait variations between the species and community levels in a mature evergreen broadleaf forest in the East Asian monsoon region. These findings shed light on the predominant role of soil phosphorus on plant functional trait variations in mature subtropical forests, providing new insights for models to incorporate soil phosphorus constraint in predicting future vegetation dynamics.

Region-dependent regulation of acute ethanol on γ oscillation in the rat hippocampal slices - Zhihua Liu; Feng Ren; Bin Yang; Hongxing Zhang; Fangli Guo; Xiangyang Zhang; Chengbiao Lu; Ruiling Zhang (Psychopharmacology, 2020)

De novo RNA-seq and functional annotation of Ornithonyssus bacoti - DongLing Niu; RuiLing Wang; YaE Zhao; Rui Yang; Li Hu (Experimental and Applied Acarology, 2018)

Occurrence, Distribution and Ecological Risks of Fluoroquinolone Antibiotics in the Dongjiang River and the Beijiang River, Pearl River Delta, South China - Ruiling Zhang; Ruijie Zhang; Shichun Zou; Ying Yang; Jun Li; Yinghui Wang; Kefu Yu; Gan Zhang (Bulletin of Environmental Contamination and Toxicology, 2017)

cDNA library construction of two human Demodexspecies - DongLing Niu; RuiLing Wang; YaE Zhao; Rui Yang; Li Hu; YuYang Lei; WeiChao Dan (Acta Parasitologica, 2017)
The research of

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Influences of topographic index distribution on hydrologically sensitive areas in agricultural watershed - Lianqing Xue; Ruiling Bao; Thomas Meixner; Guang Yang; Jingnan Zhang (Stochastic Environmental Research and Risk Assessment, 2014)

The Interaction of Flavonoid-Lysozyme and the Relationship Between Molecular Structure of Flavonoids and Their Binding Activity to Lysozyme - Ran Yang; Lanlan Yu; Huajin Zeng; Ruiling Liang; Xiaolan Chen; Lingbo Qu (Journal of Fluorescence, 2012)